Evaluating topical JAK inhibitors as a treatment option for atopic dermatitis. (4th March 2022) - Fardos, Mohammad I.; Singh, Rohan; Perche, Patrick O.; Kelly, Katherine A.; Feldman, Steven R.
ABSTRACT: Introduction: Atopic dermatitis (AD) is a chronic, inflammatory skin condition mediated by cytokines that utilize the Janus Kinase/Signal Transducer and Activator of Transcription (JAK-STAT) signaling cascade. Topical JAK inhibitors are an emerging alternative in the treatment of AD. Areas Covered: This expert review presents an overview of the underlying molecular pathophysiology of AD, current standards of care, and evaluation of the efficacy and safety of topical JAK inhibitors. A PubMed database search was utilized with a focus on the evidence from double-blind, randomized Phase I, II, and III clinical trials published between January 2015 and July 2021. Expert Opinion: Current topical therapies for AD are efficacious but limited by their adverse side effects. Long-term topical corticosteroid use leads to loss of pigmentation, striae, and skin atrophy. Patients may be concerned about topical calcineurin inhibitors' black box warning of increased risk of malignancy. Topical crisaborole, a phosphodiesterase four inhibitor, is limited by application site burning. Topical ruxolitinib is a JAK inhibitor comparable to triamcinolone in efficacy without the adverse effects seen with long-term topical corticosteroid use. Although topical JAK inhibitors have promising efficacy and safety profiles, poor medication adherence common to topical treatments may limit their utility in a clinical setting.